2014
DOI: 10.1038/srep04005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentration gradient on ionic current rectification in polyethyleneimine modified glass nano-pipettes

Abstract: Ion current rectification dependent on the concentration gradient of KCl solutions was systematically investigated in polyethyleneimine modified glass nano-pipettes with inner diameter of 105 nm. Peak shape dependence of the rectification factor on outer KCl solution concentration was observed when inner KCl solution with concentration from 1 mM to 500 mM was used. The peak shape dependence was also observed when the concentrations of the inner and outer KCl solutions were identically controlled. The peak shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Yet, the system still suffers from some intrinsic limitations, such as vulnerability to external perturbations including pH, temperature, and mechanical vibration. These drawbacks could be readily overcome in solid-state nanopores, which are usually made from durable inorganic and polymeric materials like silicon [13], silicon nitride [14], and polyethylenimine [34]. In Zhang et al [35] discovered that substituting the electrolyte solution of KCl with MgCl 2 could slow down the DNA mobility by three times, owing to the reduced charge density on the DNA backbone derived from Mg 2?…”
Section: Phi29 Connector Nanoporementioning
confidence: 98%
“…Yet, the system still suffers from some intrinsic limitations, such as vulnerability to external perturbations including pH, temperature, and mechanical vibration. These drawbacks could be readily overcome in solid-state nanopores, which are usually made from durable inorganic and polymeric materials like silicon [13], silicon nitride [14], and polyethylenimine [34]. In Zhang et al [35] discovered that substituting the electrolyte solution of KCl with MgCl 2 could slow down the DNA mobility by three times, owing to the reduced charge density on the DNA backbone derived from Mg 2?…”
Section: Phi29 Connector Nanoporementioning
confidence: 98%
“…Further theoretical study is necessary in order to estimate ρ and v. Finally, we address the extensive prospect of this study. We used rare gases for the evaluation of nanopipettes because they are inert, and charged or polarized molecules could rectify gas flow through charged nanopipettes like ICR in liquid, 14) which will be a future interesting study of the gas flow through nanospace, related to the study of nanopore sequencing. 31) Sugimoto et al observed the long dwelling time of NO gas in a glass capillary and showed that the dwelling time determines the response time and time of flight through the capillary, 27) which indicates the possibility of rectifying gas flow through charged nanopipettes.…”
Section: Discussionmentioning
confidence: 99%
“…13) Deng et al reported the dependence of ICR on the concentration gradient of KCl solutions in polyethyleneimine-modified glass nanopipettes. 14) Yuill et al demonstrated the application of nanopipettes as electrospray ionization emitters for mass spectrometry. 15) Moreover, microinjection is a useful method of transfection to cells, 16) and the viability of cells after the microinjection is not sufficiently high to obtain statistical and quantitative results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, in order to determine the constants 12 , aaand d , the following transformed conditions (13) -(14) should be applied on relation (26) according to:…”
mentioning
confidence: 99%